AB0359 Assessing depression in patients with established rheumatoid arthritis-how do different approaches compare?. (15th June 2017) - Hider, SL; Ryan, S; Dale, N; Stanyer, N; Machin, A; Chew-Graham, CA
Abstract : Background: Depression is common in patients with rheumatoid arthritis and negatively impacts on their quality of life and disease outcomes, including disease activity and treatment response. Several case-finding tools for depression are available, including the PHQ2, which is both valid (1) and easy to use. Objectives: The aim of this study was to compare the prevalence of depression using case finding tools and self-report measures in patients with established RA. Methods: Patients with established RA, attending a nurse-led annual review clinic, which aimed to offer patients a holistic review, were asked to complete a short questionnaire including demographics and self-reported comorbidity. The presence of depression was assessed in 3 ways a) PHQ2 score ≥3 b) Self recorded "ever" depression using the self-administered report comorbidity questionnaire (2) and c) Self report health status using the EQ5D - which includes a statement regarding current anxiety/depression (dichotomised into no anxiety/depression vs. slight/moderate/severe/extremely anxious or depressed. Ethical approval was obtained (15-WS-0063). Results: 179 RA patients provided data. Of these 119 (66%) were female and the mean (sd) age was 67.1 (11.7) years. 59 patients (33%) reported they had ever had depression using the self-report comorbidity questionnaire and 25 (14%) indicated they were currently receiving treatment. 68 (38%) indicated they were currently slightly (or more) anxious or depressed when assessed with the EQ5D. 37 (21%) scored positively on the PHQ2. There was good concordance between the PHQ2 and EQ5D at higher levels of depression, in that all those with severe or extreme anxiety or depression on EQ5D also scored positively on the PHQ2. However, of those with moderate anxiety/depression on EQ5D, 4/14 patients scored less than 3 using the PHQ2 score. Conclusions: Depression is common in patients with established RA. Use of the PHQ2 case-finding questions in patients with established RA, may help clinicians identify patients who may benefit from more detailed assessment of mood and interventions to improve their outcomes. Reliance should not be placed on a single tool, and exploration of mood should be part of routine assessment of a patient with RA. References: Meader N, et al. BJGP 2011:61: 733–734. Sangha O, et al.Arthritis Rheum 2003;49:156–63. Acknowledgements: ND was funded by the Haywood Foundation. CCG is funded by the National Institute for Health Research (NIHR) Collaborations for Leadership in Applied Health Research and Care West Midlands. The views expressed are those of the authors and not necessarily those of the NHS, NIHR or the Department of Health. Disclosure of Interest: None declared